2020
DOI: 10.1167/iovs.61.2.34
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Retinal Blood Flow in a Feline Retinal Vein Occlusion Model as Measured by Doppler Optical Coherence Tomography and Optical Coherence Tomography Angiography

Abstract: PURPOSE. We aimed to observe longitudinal changes in retinal blood flow (RBF) and structural transformations in capillaries using Doppler optical coherence tomography (DOCT) and optical coherence tomography angiography (OCTA) in a feline retinal blood occlusion (RVO) model. METHODS. RVO was induced by argon green laser photocoagulation (PC) in six eyes of six cats. RBF was measured at a first-order retinal artery and vein by a DOCT flowmeter, and structural changes in the capillaries around the occluded vessel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Wada et al. made similar observations in their experiments on feline RVO [ 14 ]. However, due to the characteristics of OCTA, when retinal blood flow is slow, it does not always depict the actual state of retinal blood flow.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Wada et al. made similar observations in their experiments on feline RVO [ 14 ]. However, due to the characteristics of OCTA, when retinal blood flow is slow, it does not always depict the actual state of retinal blood flow.…”
Section: Discussionsupporting
confidence: 61%
“…Wada et al. utilized OCTA in a feline RVO model [ 14 ]. While they precisely described the vascular changes after PC, the feline model had limitations in the lack of antibodies against various proteins as well as unknown mRNA sequences that would enable further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Collateral vessels mature over 6 to 24 months after BRVO onset [9]. In contrast, previous animal studies have shown that collateral vessels were observed within 3 to 5 days after BRVO [84,96,97]. One study [97] found that collateral vessels developed from the preexisting capillary networks up to 4 days after laser-induced vein occlusion, matured by day 7, and were pruned on day 14 to a size similar to the original retinal vein.…”
Section: Collateral Vesselsmentioning
confidence: 98%